The Utility Incommensurability Thesis: The Analytics of Preferences à la Adam Smith - Elias L. Khalil (Œconomia)
This article identifies friendship-and-love as an input that produces what this article calls “transcendental utility”. Such input differs from substantive inputs—e.g., food and clothes—that produce what economists call “utility” and what this article dubs “substantive utility”. While there is a link between transcendental and substantive utilities, the main thesis of this article is that the two utilities are incommensurable. The article’s contribution lies in justifying the proposed utility incommensurability thesis. It does so through the exploration of Adam Smith’s concept of “mutual sympathy”. While Smith’s scholars have started to pay attention to this concept, they do not appreciate its importance in uncovering the nature of the friendship-and-love utility, especially how such utility is incommensurable with substantive utility.